2015
DOI: 10.1108/wjemsd-07-2014-0020
|View full text |Cite
|
Sign up to set email alerts
|

Corrupting activities and economic development

Abstract: Purpose – The purpose of this paper is to explore the relationships of different types of corruption and selected economic measures that appear to contribute to a country’s sustainable economic development. Design/methodology/approach – The research used selected data from the World Economic Forum Executive Opinion Survey on corruption activities (Irregular Payments and Bribes, the Diversion of Public Funds, Organised Crime, and Favourit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…These organisations are recognised for gathering and publishing relatively valid and reliable information. While not perfect, WEF and WDI appear to be the best sources of corruption and tax evasion triggering (economic) data currently available to researchers (Anderson, 2015).…”
Section: Data and Data Sourcesmentioning
confidence: 99%
See 2 more Smart Citations
“…These organisations are recognised for gathering and publishing relatively valid and reliable information. While not perfect, WEF and WDI appear to be the best sources of corruption and tax evasion triggering (economic) data currently available to researchers (Anderson, 2015).…”
Section: Data and Data Sourcesmentioning
confidence: 99%
“…The study relied on the corruption measures adopted by Anderson (2015). The WEF collects survey data on different dimensions of corruption via its Executive Opinion Survey (World Economic Forum, 2014, pp.…”
Section: Corruption Indicatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The World Bank is a reputable organisation for collating and disseminating credible and useful information. Anderson (2015) maintains that though the WDI data may not be perfect, they represent the most credible sources of FDI and FD data relied upon by researchers the world over.…”
Section: Data and Data Sourcesmentioning
confidence: 99%
“…I do not know: the survey showed that the high rate of the participants does not know about the organization code of conduct and internal policy. This rate as explained in table (6) shows the huge gap between the efficiency of implemented activities in the reality and the organization management board.…”
mentioning
confidence: 98%